1997
DOI: 10.3109/02844319709010502
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Bone Distraction in Craniosynostosis

Abstract: Seven patients with craniosynostosis (mean age 8 years, Apert syndrome, n = 4, Crouzon's disease, n = 3) underwent lengthening of the skull by gradual bone distraction. Three patients (group A) were treated by coronal craniectomy reaching the orbital fissure and gradual bone distraction. The other four (group B) underwent monobloc craniofacial disjunction and gradual bone distraction. The patients' progress was monitored clinically as well as by radiographs and photographs. The results showed that craniofacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…After a report by Lauritzen et al [19] in 1998 who showed the possibility of distraction employing springs rather than distractors, Guimarães-Ferreira et al [21] further augmented the above results with observations that distraction of the fused sagittal suture alone with springs after craniectomy afforded favorable results in patients with sagittal craniosynostosis. A remarkable report was published by do Amaral et al [20] who performed successful suturectomy and distraction only in 7 children with syndromic craniosynostosis, but which did not gain attention because of the lack of exact methods and vectors, despite being an unprecedented study at that time. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After a report by Lauritzen et al [19] in 1998 who showed the possibility of distraction employing springs rather than distractors, Guimarães-Ferreira et al [21] further augmented the above results with observations that distraction of the fused sagittal suture alone with springs after craniectomy afforded favorable results in patients with sagittal craniosynostosis. A remarkable report was published by do Amaral et al [20] who performed successful suturectomy and distraction only in 7 children with syndromic craniosynostosis, but which did not gain attention because of the lack of exact methods and vectors, despite being an unprecedented study at that time. …”
Section: Discussionmentioning
confidence: 99%
“…Complications of distraction osteogenesis that have been found in previous studies are pin site infection, meningitis, discharge, device exposure, bone fracture, dislocation, shaft slippage, distortion of device, and distractor breakage [4,5,6,8,20,33,34,35]. In our present study of 22 TSDO procedures, we observed 2 cases (9.1%) of pin site discharge which seemed to be similar to the previously reported 11.1–21.1% after distraction osteogenesis methods [4,8,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distraction osteogenesis for cranioplasty can expand cranial volume and suppress operative blood loss [13,14,15,16,17,18,19]. This technique is routinely performed to correct other cranial deformities but is not suitable for use in scaphocephaly.…”
Section: Introductionmentioning
confidence: 99%
“…18,35 Distraction osteogenesis is the surgical induction of bone growth by applying distractive force across an osteotomy site, and this technique is becoming more common for expanding the cranium and for advancing the midface. 2,14,15,22,29,31,33,38,40,42,49 Distraction osteogenesis is a historical outgrowth of various methods of fracture reduction and retention that date back almost 2000 years. 48 Elective osteotomy combined with mechanical traction was used for femoral lengthening as early as 1905; 11 however, this technique was abandoned because of a high complication rate.…”
mentioning
confidence: 99%